A influência da complexidade sociopolítica relacionada aos stakeholders na gestão de projetos de tecnologia: estudo de caso em uma instituição financeira - Vieira, Tatiana Paula da Costa (2016)
This study of explanatory case, included in the project management department, has as the main goals which are and who are the stakeholders of the systemic development projects of the financial institutution being studied, which are and how the extent indicators of the socialpolitical complexity impact the management conplexity of the projects and which actions were taken by the projects managers to mitigate the complexity related to these indicators, using mainly, as a theoric reference, seminal publications referred to the stakeholders and the project management complexity. In order to achieve this goal, deeply semi-organized interviews were done with 15 professionals who work with the technology in this institution, analysis of internal and external public documents and observation. The results show that the project management team, suppliers and trade partner, operation managers, other interested parts, portfolio managers, programming managers and the project office were not totally recognized by all the interviewed people. Moreover, it was verified all the indicators of the social-political complexity related to stakeholders (existence of hidden agenda, power conflicts, confliting priorities and requeriments among the projects, resistence, interference and litlle committal from the interest parts in the project and existence of a sênior management support) influence the complexity in the project management and indicating the existance of the social-political dimension complexity in these kinds of projects. Lastly, it was also verfied that the project managers are able to use some actions to soften the impacts of this complexity caused by the stakeholders, such as: allocate full time resource in the project, determine roles and responsabilities to the involved people in the project, scale the problems to the sponsor or superior competence, determine sharing goals among the project stakeholders.